Design of urban runoff pollution control based on the Sponge City concept in a large-scale high-plateau mountainous watershed: a case study in Yunnan, China - Zhenyu Zhang (IWA Publishing, 2021)
China recently commenced the Sponge City initiative for the effective management of urban stormwater runoff. Numerous studies have been carried out to evaluate the cost-effectiveness of low impact development (LID) practices in Sponge City planning and implementation. However, most of the studies were at the site- or subcatchment scale, and few were conducted at the watershed scale, given the dramatically increased routing complexity and number of decision variables. This study demonstrates the cost-effective Sponge City planning process for a 25.90 km2 high-plateau watershed in southwest China. The Stormwater Management Model was coupled with the System for Urban Stormwater Treatment and Analysis Integrated (SUSTAIN) model to perform both continuous simulations and watershed-level optimization analyses, using the reduction of 85% annual runoff volume as the optimization target. Based on over 11,000 optimization runs, a near-optimal aggregated LID scenario was identified for each subcatchment. The aggregated LID size was first converted into a generic LID storage volume for individual subcatchments, and the storage volume was then disaggregated into site-level LID layouts regarding specific site conditions. The disaggregated LID layout yielded an annual average runoff volume reduction of 87.61% and close to 85% reduction for the annual average total suspended solids, total nitrogen, and total phosphorus loads. The systematic approach outlined in this study could be used for watershed-level Sponge City planning and implementation analyses in other cities.